The Sarkarian proposal and molecular-genetic reductionism - Francese, Christian Federico (2021)
One of the most interesting and influential proposals on the subject of reductionism in Biology has been presented by Sahotra Sarkar, mainly in his book Genetics and Reductionism. There the author proposes a general model of reduction and uses it to analyze the reductive relationships between genotype and phenotype, and of Biology with Chemistry and Physics. One of his thesis is that both reductionisms are entirely different conceptual approaches with no relation between them. In this article we critically explore the Sarkarian thesis. Here we argue that the two reductionisms are deeply interconnected and that together they shape an extended vision in contemporary Biology as well as fundamental in current biotechnological projects. We have called such perspective “genetic-molecular reductionism” and characterized from the general Sarkar reduction model. The work carried out allows us to expose both the scope of the Sarkarian proposal itself and some remarkable characteristics of a prevalent perspective in Biology.